RICH Economic Games for Networked Relationships and Communities: Development and Preliminary Validation in Yasawa, Fiji. Issue 2 (May 2017) - Gervais, Matthew M.
Experimental economic games reveal significant population variation in human social behavior. However, most protocols involve anonymous recipients, limiting their validity to fleeting interactions. Understanding human relationship dynamics will require methods with the virtues of economic games that also tap recipient identity-conditioned heuristics (RICHs). This article describes three RICH economic games—an allocation game, a taking game, and a costly reduction game—that involve monetary decisions across photos of one's social network, integrating recipient identities while maintaining decision confidentiality. I demonstrate the ecological validity of these games in a study of male social relationships in a rural Fijian village. Deciders readily map these games onto daily life, and target earnings vary widely; consistent with ethnography, relative need is the primary rationale for decisions across the games, while both punitive and leveling motives drive reduction behavior. Consequently, altruism and spite are both elevated relative to anonymous target games in neighboring villages.